Leukocyte Bactericidal Activity in Chronic Granulomatous Disease: Correlation of Bacterial Hydrogen Peroxide Production and Susceptibility to Intracellular Killing - Mandell, Gerald L. (1969)
Susceptibility of bacteria to intracellular killing by polymorphonuclear leukocytes from a patient with chronic granulomatous disease could be correlated with bacterial hydrogen peroxide production.